Circulating biomarkers of gastroenteropancreatic and lung neuroendocrine neoplasms: "The times they are a changin". (June 2021) - Modlin, Irvin M.; Kidd, Mark; Bodei, Lisa; Malczewska, Anna; Kitz, Alexandra; Oberg, Kjell
Abstract: Biomarkers that are secretory monoanalyte products of gastroenteropancreatic and bronchopulmonary or lung neuroendocrine tumors (NETs) have significant limitations in clinical utility. The assessment of secretory activity provides little information in regard to tumor biology. Furthermore, ∼50% of NETs have measurable secretory products. Molecular genomic identification in blood ( NETest liquid biopsy) of the regulators of tumor biology provide multianalyte, real-time assessment of tumor status. These data represent the assessment of ∼2000 NETs over 5 years and demonstrate the NETest has ∼95% accuracy in GEP-NET andbronchopulmonary neuroendocrine tumor diagnosis, is >90% concordant with imaging, and is 90% accurate in differentiating stable from progressive disease. The comparable metrics for Chromogranin A are all ∼50%. In addition, the NETest identifies complete surgical resection in 100% and has a 98% efficacy in monitoring peptide receptor radionuclide therapy efficacy. Real-time liquid biopsy assessment of NET disease provides a noninvasive, accurate strategy to define the NET patient journey. "The times they are a changin"….